2022
DOI: 10.1200/op.21.00274
|View full text |Cite
|
Sign up to set email alerts
|

Survival in the Real World: A National Analysis of Patients Treated for Early-Stage Breast Cancer

Abstract: PURPOSE: Many patient population groups are not proportionally represented in clinical trials, including patients of color, at age extremes, or with comorbidities. It is therefore unclear how treatment outcomes may differ for these patients compared with those who are well-represented in trials. METHODS: This retrospective cohort study included women diagnosed with stage I-III breast cancer between 2005 and 2015 in the national CancerLinQ Discovery electronic medical record–based data set. Patients with comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The multidecade issue of clinical trial accrual has the potential to exacerbate clinical outcomes (eg, disease, disability, and death) in drugs not typically tested in underrepresented patient populations. 26,27 We expected and found Black patients and patients in areas of higher disadvantage had lower odds of enrollment; however, we found that patients living in rural areas had similar odds of enrollment. We identified that different patient populations had differing odds of retention along the trial enrollment process.…”
Section: Discussionmentioning
confidence: 57%
“…The multidecade issue of clinical trial accrual has the potential to exacerbate clinical outcomes (eg, disease, disability, and death) in drugs not typically tested in underrepresented patient populations. 26,27 We expected and found Black patients and patients in areas of higher disadvantage had lower odds of enrollment; however, we found that patients living in rural areas had similar odds of enrollment. We identified that different patient populations had differing odds of retention along the trial enrollment process.…”
Section: Discussionmentioning
confidence: 57%
“…These results are at odds with the systematic review of trials on de-escalation in the duration of adjuvant trastuzumab therapy 14 , where a shorter duration of adjuvant trastuzumab is associated with significantly worse DFS and OS. Other studies and meta-analyses 12 , 24 , however, have shown non-inferiority of 6 months compared to 12 months. These results should be interpreted with caution, as they are based primarily on the Persephone trial 12 , an older trial that employed chemotherapy-trastuzumab regimens considered nonstandard (taxane-free anthracyclines in 90% and sequential trastuzumab in 53% of cases), in a relatively low-risk population (59% of node-negative patients).…”
Section: Discussionmentioning
confidence: 90%
“…Early stage breast cancer is more commonly diagnosed than more advanced breast cancer, but around 20% of these patients have recurrence [ 31 ]. CTCs in the early stages of breast cancer can generate micrometastases and thus are the seeds of the metastatic cascade.…”
Section: Ctcs In Early Stage Breast Cancermentioning
confidence: 99%